The Political Economy of Fiscal Reform: The Case of Colombia, 1986-2006 - Mauricio Olivera; Monica Pachon; Guillermo Perry (Inter-American Development Bank (IDB), 2010)
This paper explores the characteristics of the political economy process that conditioned the scope and success of the combination of fiscal reforms before and after Colombias 1991 constitutional reforms. Using formal analysis of reforms and interviews with actors, reforms in taxation, decentralization, the budgetary process and pensions are examined in times of political crisis, economic crisis, and economic boom. The results generally confirm the hypothesis that increased political fragmentation and limited unilateral executive power after the 1991 reforms restricted the extent of reforms, particularly in tax law. Nonetheless, the enactment of piecemeal reforms was encouraged by crisis conditions.
Keywords: H20; H71; H77; 330; Policymaking process; Political economy; Structural reform; Colombia